Worksite Health and Wellness in the European Union - Guazzi, Marco; Faggiano, Pompilio; Mureddu, Gianfranco F.; Faden, Giacomo; Niebauer, Josef; Temporelli, Pierluigi L. (Progress in cardiovascular diseases, 2014)
In recent years, trends in cardiovascular disease (CVD) incidence and prevalence in Europe have shown a significant decline. Nonetheless, CVD still remains the main cause of morbidity and mortality and, as such, more efficient intervention strategies are needed. In this context, workplace health promotion is universally viewed as a potential resource for further reducing CVD burden. Currently, the most active organizations for promoting workplace health promotion are the European Agency for Safety and Health at Work, the European Network for Workplace Health Promotion and the Wellness International. The idea of wellbeing in the workplace has multiple meanings across organizations and countries in Europe and no comprehensive surveys examining its exact prevalence and overall impact are currently available. This review will describe the current state of workplace health promotion in Europe and address future directions for this potentially important intervention strategy.